2019
DOI: 10.1186/s13098-019-0410-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and adipokine levels were significantly correlated in diabetic patients with hyperglycemic crises

Abstract: BackgroundTo investigate the relationship between blood adipokine level and oxidative stress in diabetic patients with hyperglycemic crises before and after treatment.MethodsWe measured superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, total antioxidant capacity (TAC), and levels of 8-iso-prostaglandin F2α (8-iso-PGF2α), adiponectin, leptin, and resistin in 63 diabetic patients with hyperglycemic crises.ResultsPrior to treatment, patients with hyperglycemic crises had significantly lower seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Both seizure activity and fever-illness context have common stress-related mechanisms with high metabolic states, hypoperfusion, relative hypoxic states due to rising oxygen demands needed for additional energy supply, and accelerated glycolysis [1,[4][5][6][7][8][9][10][11]. The oxidative stress is playing a key role as a common pathway for febrile seizures and stress hyperglycemia [8,12,13]. Moreover, in stress hyperglycemia, cytokines and hormones, interact in a complex manner supporting gluconeogenesis, glycogenolysis, and insulin resistance as pathogenic hallmarks [1,[4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Both seizure activity and fever-illness context have common stress-related mechanisms with high metabolic states, hypoperfusion, relative hypoxic states due to rising oxygen demands needed for additional energy supply, and accelerated glycolysis [1,[4][5][6][7][8][9][10][11]. The oxidative stress is playing a key role as a common pathway for febrile seizures and stress hyperglycemia [8,12,13]. Moreover, in stress hyperglycemia, cytokines and hormones, interact in a complex manner supporting gluconeogenesis, glycogenolysis, and insulin resistance as pathogenic hallmarks [1,[4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Adipokines, such as leptin, resistin, adiponectin, chemerin, omentin, and visfatin, play a critical role in the development of complications related to obesity and inflammatory conditions [13]. In addition, they are also involved in other functions of the organism including those pertinent to the gonadal and hypothalamic-pituitary axis, both in females and in males.…”
Section: Introductionmentioning
confidence: 99%
“…In SHR, oxidative stress appears to be the cause of hypertension development on a larger scale and major effect of PPAR-γ activation is the reduction of oxidative stress levels (68). Recent epidemiological studies together with human diabetic models have suggested an association between adiponectin concentration and oxidative stress, thus, decreased circulating adiponectin levels predominates in increased oxidative stress, which are closely linked with metabolic syndrome (69), (12), and a the key feature of increased production of ROS and proin ammatory pathways (11). Production of ROS reduces bioavailability of NO due to uncoupling of eNOS, with enhanced levels of superoxide anions leading to formation of peroxynitrite, thus aggravates the impairment of eNOS activity and reduces NO production (70).…”
Section: Adiponectin Concentration In Plasma and Lipid Pro Lementioning
confidence: 99%
“…Additionally, recent studies have shown that oxidative stress negatively regulates the adiponectin gene expression (10), therefore, its concentration in plasma impacts the oxidative stress (11), (12).…”
Section: Introductionmentioning
confidence: 99%